The strategy of the European Union between expansion and decline. (Journal of Human Sciences, 2022)
This study dealt with the strategy of the European Union between expansion and confinement, as a discrepancy in the ambitions of the European continent has emerged since the era of interdependence policies in the mid-fifties of the last century, The emergence of the era of European-European rapprochement and the emergence of the nation-state. This rapprochement established the principle of cooperation and economic partnership between a number of countries in bilateral and collective unions, leading to the group of iron and steel, and from the European Common Market, to what became known as the European Union at the beginning of the nineties of the last century, which Opening horizons and renewing hopes for the peoples of the European continent However, this union witnessed several failures, including the failure of the United Kingdom to accede to the single European currency “Euro” but rather kept its currency “sterling”, and the divergence and failure increased through the “Brexit” project through which the United Kingdom exited from the European Union in 2019, and the war The Russian-Ukrainian cast a shadow over the course of the European Union, with the fear of a number of European countries, of what this war might lead to and constitute a regression and a regression of the strategy that the European Union aspired to, and accordingly this study was divided into a number of investigations.